Situacional diagnosis of consultation in the basic health network in the Municipality of Belém, State of Pará, Brazil (Research, Society and Development, 2021)
The objective was to carry out the situational diagnosis of the pharmaceutical consultation in the Basic Health Units (BHU) in the city of Belém. This is a cross-sectional study of a descriptive character with a qualitative approach, carried out through data collection, from July to August 2020, through the application of an adapted questionnaire, based on the instrument used in the National Survey on Access, Use and Promotion of Rational Use of Medicines (PNAUM), which was composed of eighteen (18) open and closed questions about the activities of management actions and assistance actions, managed by pharmacists in the UBS, seeking to obtain information about the real scenario of the activities performed by these professionals, as well as, to identify their clinical performance in a more comprehensive way and how it is performed in the work routine. . Among the results, it was found that only three UBS develop practices related to clinical pharmaceutical services. Among the reasons for the absence of this practice in the other UBS, the lack of infrastructure, the lack of human resources and the unavailability of time by the pharmaceutical professional were identified. The executed proposal is an initial strategy for the subsequent implementation of the pharmaceutical consultation service in the municipal health network in Belém, considering the evidence through the situational diagnosis that proves the absence of the service in a standardized way.